A study on Design and Development of Harmonium and Its Types - V. Brinda; Dr.M.A. Bhageerathi (International journal of economic perspectives, 2022)
The sound a harmonium brings is unlike anything else in existence. When you hear it you feel you are being transported to another place and time. The keyboard comprises black and white keys. The white keys are for pure notes and the blacks ones are for soft ones. However, this is not applicable if the scale is changed. The main purpose of this paper to know basic components of harmonium and types of harmonium, history of harmonium those who want to learn in the beginning stage they can utilize this article and it helps to understand the famous players in India. The ever-changing music world has gone through some great inventions in the past that have changed the entire approach to different music techniques, and harmonium is one of them. Also known as reed organ, melodeon, or pump organ, harmonium history is commonly traced back to Indian origin, which is not true. Though most music historians associate harmonium with Indian origin, but this music tool belonged to Europe. It was used in the churches in Europe during the middle ages.